Algorithmic Integration of Budgets into Strategic Enterprise Management - B. E. Odintsov (Управленческие науки, 2019)
The author offers new approaches to dealing with the strategic and operational management of the company. The model of guaranteed algorithmic impact of strategic requirements (recommendations) expressed in specific indicators on monthly budgeting process is offered in the article. The organic interaction of these control types will allow management to implement model developments systematically and consistently in the enterprise. Embedding monthly budgets in strategic management involves the creation of intellectual information system, the core of which would be the hierarchical knowledge base that provides algorithmic communication between the strategy and budget. In addition, the database of formulas must be created which are designed for monthly calculations of indicators that are defined by the strategic goal. The provided in the article technology of fuzzy hierarchical search of restrictions on a number of key fiscal indicators clearly demonstrates the process of smoothing conflicts and resolving problems encountered during the adaptation of target strategic requirements to the real possibilities of the enterprise.